Mothers’ practices in complementary feeding (MP-ASI) among infants in the service area of Banda Aceh City Primary Health Center - Mutazalifa Istammah; Yuni Arnita; Neti Hartaty (PT WIM Solusi Prima, 2026)
Inappropriate complementary feeding practices in terms of timely initiation, portion size, feeding frequency, food variety, and texture may affect infants’ nutritional status and increase the risk of health problems. This study aimed to describe maternal behavior in complementary feeding among infants aged 6–24 months. A descriptive quantitative study design was employed using proportional sampling, involving 201 mothers in the working area of Public Health Center, Banda Aceh City. Data were collected using a complementary feeding behavior questionnaire that had been tested for validity and reliability and were analyzed using univariate analysis. The results showed that the majority of mothers (69.2%) demonstrated inappropriate complementary feeding practices. Most complementary feeding was initiated before the age of six months, with inadequate food variety and inappropriate texture for the infants’ age, as well as suboptimal portion size and feeding frequency. These findings indicate that complementary feeding practices among infants remain inconsistent with recommended guidelines. Therefore, strengthening educational interventions for mothers regarding appropriate complementary feeding principles is necessary to support optimal growth and prevent the risk of undernutrition in infants. Health workers are expected to enhance nutrition education and routinely monitor infants’ nutritional status, while families are encouraged to actively support complementary feeding practices that adhere to appropriate timing, portion size, frequency, variety, and texture to promote optimal infant growth and development.